Obtenção de mantas de poli (ácido lático) por fiação por sopro em solução e sua caracterização para uso em sistemas de microfiltração - Azerêdo, Marina Soares de (2020)
In order to remediate the difficulty of access to safe drinking water by 1/3 of the world population and the need to use new processes for obtaining materials, membranes produced by solution blow spinning (SBS) have a great potential for use in liquid filtration due to their small pores (0,2 to 10 µm) and high porosity (>80%), being capable of retaining particles and even microorganisms. In this context, the objective of this work was the production and characterization of poly (lactic acid) (PLA) mats obtained by SBS technique to be morphologically, thermally and mechanically evaluated, as well as to observe their water flux and rejection / retention properties. First, the concentrations of 10 and 16% w/v of PLA/dichloromethane solution were selected due to being the limit concentrations of the semi-diluted regime. Then, process parameters such as injection rate and air pressure were selected from an experimental design of type 23, where the effect of these properties and the solution concentration on the fiber diameters was observed. The non-woven mats produced were evaluated by scanning electron microscopy (SEM), thermal analysis (TGA and DSC), tensile testing, water flux and rejection performance of alumina particles and retention of E. coli bacteria. It was observed that the lower concentration of polymeric solution led to the obtention of mats with smaller average fiber diameter, greater crystallinity, impacting on their greater tensile strength. The results of water flux showed that the mats obtained from the solution with higher polymer concentration had less resistance to the water flow, being an indication of larger pore diameters. In rejection tests of alumina particles and retention of bacteria, both types of mats had similar performances, with ~34% of rejection of alumina particles and 7% of retention of bacteria. Therefore, this work correlated structure-processing-properties in liquid filtration of PLA mats obtained by the promising technique of solution blow spinning, which presents a series of advantages over the common techniques to obtain nanofibrous membranes.